Janmashtami celebrations at Ram Mandir in Versova - Mumbai Archive Project Team (Jio Institute, 2024)
Janmashtami celebrations at Versova are centred around the Ram Mandir. The main deity of the temple is Lord Ram, along with other deities such as Sita, Lakshman, and Hanuman.